Audio analysis of the effects of heavy violin practice mutes: spectral and loudness changes - da Silva Evangelista Marcus Vinicius; Freire Sérgio (Acta Acustica, 2025)
The article discusses the effects of heavy practice mutes on violin sonority. Objective data (Long Term Average Spectrum and Loudness) from a parameterized sampling made with different types of performance and practice mutes, as well as modified devices and replicas made with lead, were employed in a comparative study. Specific effects of heavy practice mutes, such as the absence of energy transfer to the low frequency region, were observed. The text presents the mutes and describes the methodology, data processing, and the acoustic descriptors employed, followed by a discussion of the results.